Isolation and Characterization of Ischemia-Derived Astrocytes (IDAs) with Ability to Transactivate Quiescent Astrocytes - Villarreal, Alejandro; Rosciszewski, Gerardo; Murta, Veronica; Cadena, Vanesa; Usach, Vanina; Dodes-Traian, Martin M.; Setton-Avruj, Patricia; Barbeito, Luis H.; Ramos, Alberto J. (Frontiers in Cellular Neuroscience, 2016)
Reactive gliosis involving activation and proliferation of astrocytes and microglia, is a widespread but largely complex and graded glial response to brain injury. Astroglial population has a previously underestimated high heterogeneity with cells differing in their morphology, gene expression profile and response to injury. Here, we identified a subset of reactive astrocytes isolated from brain focal ischemic lesions that show several atypical characteristics. Ischemia-derived astrocytes (IDA) were isolated from early ischemic penumbra and core. IDA did not originate from myeloid precursors, but rather from pre-existing local progenitors. Isolated IDA markedly differ from primary astrocytes, as they proliferate in vitro with high cell division rate, show increased migratory ability, have reduced replicative senescence and grow in the presence of macrophages within the limits imposed by the glial scar. Remarkably, IDA produce a conditioned medium that strongly induced activation on quiescent primary astrocytes and potentiated the neuronal death triggered by oxygen-glucose deprivation (OGD). When re-implanted into normal rat brains, eGFP-IDA migrated around the injection site and induced focal reactive gliosis. Inhibition of gamma secretases or culture on quiescent primary astrocytes monolayers facilitated IDA differentiation to astrocytes. We propose that IDA represent an undifferentiated, pro-inflammatory, highly replicative and migratory astroglial subtype emerging from the ischemic microenvironment that may contribute to the expansion of reactive gliosis.